Programmed Exercise Attenuates Familial Hypertrophic Cardiomyopathy in Transgenic E22K Mice via Inhibition of PKC-α/NFAT Pathway - Wang, Haiying; Lin, Yuedong; Zhang, Ran; Chen, Yafen; Ji, Wei; Li, Shenwei; Wang, Li; Tan, Rubin; Yuan, Jinxiang (Frontiers in Cardiovascular Medicine, 2022)
Familial hypertrophic cardiomyopathy (FHCM), an autosomal dominant disease, is caused by mutations in genes encoding cardiac sarcomeric proteins. E22K, a mutation in the myosin regulatory light chain sarcomere gene, is associated with the development of FHCM. However, the molecular mechanisms by which E22K mutation promotes septal hypertrophy are still elusive. The hypertrophic markers, including beta-myosin heavy chain, atrial natriuretic peptide and B-type natriuretic peptide, were upregulated, as detected by fluorescence quantitative PCR. The gene expression profiles were greatly altered in the left ventricle of E22K mutant mice. Among these genes, nuclear factor of activated T cells (NFAT) and protein kinase C-alpha (PKC-α) were upregulated, and their protein expression levels were also verified to be elevated. The fibrosis markers, such as phosphorylated Smad and transforming growth factor beta receptor, were also elevated in transgenic E22K mice. After receiving 6 weeks of procedural exercise training, the expression levels of PKC-α and NFAT were reversed in E22K mouse hearts. In addition, the expression levels of several fibrosis-related genes such as transforming growth factor beta receptor 1, Smad4, and alpha smooth muscle actin in E22K mouse hearts were also reversed. Genes that associated with cardiac remodeling such as myocyte enhancer factor 2C, extracellular matrix protein 2 and fibroblast growth factor 12 were reduced after exercising. Taken together, our results indicate that exercise can improve hypertrophy and fibrosis-related indices in transgenic E22K mice via PKC-α/NFAT pathway, which provide new insight into the prevention and treatment of familial hypertrophic cardiomyopathy.